2013
DOI: 10.1002/jgrd.50540
|View full text |Cite
|
Sign up to set email alerts
|

Robust elements of Snowball Earth atmospheric circulation and oases for life

Abstract: [1] Atmospheric circulation in a Snowball Earth is critical for determining cloud behavior, heat export from the tropics, regions of bare ice, and sea glacier flow. These processes strongly affect Snowball Earth deglaciation and the ability of oases to support photosynthetic marine life throughout a Snowball Earth. Here we establish robust aspects of the Snowball Earth atmospheric circulation by running six general circulation models with consistent Snowball Earth boundary conditions. The models produce qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
84
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(89 citation statements)
references
References 80 publications
5
84
0
Order By: Relevance
“…The Hadley circulation also affects other suggested deglaciation factors such as atmospheric dust (Abbot and Halevy, 2010) and tropical clouds . Through its impact on the tropical precipitation minus evaporation pattern, the Hadley circulation furthermore influences the flow of thick sea ice and the possibility of open narrow seaways that could serve as oases for the survival of life during Snowball events (Campbell et al, 2011;Tziperman et al, 2012;Abbot et al, 2013). Finally, the Hadley circulation plays an important role during the initiation of Snowball Earth episodes (Voigt and Marotzke, 2010;Abbot et al, 2011;Voigt and Abbot, 2012;Yang et al, 2012a, b) during which it progressively approaches the dry limit discussed here.…”
Section: A Voigt: Dynamics Of the Snowball Earth Hadley Circulationmentioning
confidence: 79%
See 3 more Smart Citations
“…The Hadley circulation also affects other suggested deglaciation factors such as atmospheric dust (Abbot and Halevy, 2010) and tropical clouds . Through its impact on the tropical precipitation minus evaporation pattern, the Hadley circulation furthermore influences the flow of thick sea ice and the possibility of open narrow seaways that could serve as oases for the survival of life during Snowball events (Campbell et al, 2011;Tziperman et al, 2012;Abbot et al, 2013). Finally, the Hadley circulation plays an important role during the initiation of Snowball Earth episodes (Voigt and Marotzke, 2010;Abbot et al, 2011;Voigt and Abbot, 2012;Yang et al, 2012a, b) during which it progressively approaches the dry limit discussed here.…”
Section: A Voigt: Dynamics Of the Snowball Earth Hadley Circulationmentioning
confidence: 79%
“…Finally, the Hadley circulation plays an important role during the initiation of Snowball Earth episodes (Voigt and Marotzke, 2010;Abbot et al, 2011;Voigt and Abbot, 2012;Yang et al, 2012a, b) during which it progressively approaches the dry limit discussed here. All of the above factors depend on the strength of the Hadley circulation, which Abbot et al (2013) found to vary by up to a factor of 4 in annual-mean and a factor of 2 in solstice conditions among comprehensive atmosphere general circulation models driven by the same idealized Snowball Earth boundary conditions. The simulations presented here suggest that this difference might, at least partly, be caused by differences in the models' treatment of vertical diffusion of momentum.…”
Section: A Voigt: Dynamics Of the Snowball Earth Hadley Circulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Under such large climate changes, substantial nonsmooth climate feedbacks are expected, and the proportionality between radiative forcing and mean surface temperature will weaken. Such climates are an active area of research with general circulation models [e.g., Abbot et al, 2013;Russell et al, 2013]. Nonetheless, radiative forcings and a climate sensitivity parameter of ≈0.5 K∕(W m −2 ) [IPCC, 2001] provide a good first-approximation estimate of climate change and are the best way of comparing the relative efficacy of different greenhouse gases.…”
Section: Discussionmentioning
confidence: 99%